Enhancing Sweet Corn (Zea mays Saccharata) Production through Standard Operating Procedure-based Cultivation Techniques - Made, Usman; Tambing, Yohanis; Idham, Idham; Haji Nasir, Burhanuddin (Journal of Community Practice and Social Welfare, 2024)
Sweet corn (Zea mays Saccharata) is a promising legume commodity suitable for agricultural business ventures. The prospect of developing sweet corn farming is bright, aiming to improve farmers' income, enhance their welfare, and contribute to national revenue. In Sidera Village, farming practices for sweet corn are predominantly conventional, lacking adherence to principles of sustainable development, characterized by the use of inorganic fertilizers and chemical pesticides not in accordance with recommendations. A community engagement program aims to assist farmers in implementing cultivation techniques following Standard Operating Procedures (SOP) to boost sweet corn production. Specific targets include enhancing farmers' knowledge and skills to increase sweet corn productivity, addressing healthy food provision and income elevation. The program is conducted in Sidera Village, Sigi Biromaru Sub-District, collaborating with the Tunas Sejahtera farmer group as partners. Methods employed encompass training, practical sessions, technology package demonstrations, pilot plots, participatory mentoring, and coaching. Training covers standardized corn cultivation systems, organic granular and liquid fertilizer development, and bio-rational pesticides. Subsequently, practical sessions, demonstrations, and pilot plot cultivation according to SOP are carried out. The program's outcome includes a 40% increase in participants' knowledge and skills in optimal sweet corn cultivation techniques, with pilot plot yields reaching 7 tons/ha of good-quality corn, thus holding significant economic value for community income enhancement.